2021
DOI: 10.1016/s2352-4642(21)00198-x
|View full text |Cite|
|
Sign up to set email alerts
|

Illness duration and symptom profile in symptomatic UK school-aged children tested for SARS-CoV-2

Abstract: Summary Background In children, SARS-CoV-2 infection is usually asymptomatic or causes a mild illness of short duration. Persistent illness has been reported; however, its prevalence and characteristics are unclear. We aimed to determine illness duration and characteristics in symptomatic UK school-aged children tested for SARS-CoV-2 using data from the COVID Symptom Study, one of the largest UK citizen participatory epidemiological studies to date. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
426
8
16

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(479 citation statements)
references
References 30 publications
29
426
8
16
Order By: Relevance
“…Authors concluded that some children who tested positive for SARS-CoV-2 experience prolonged illness duration. Reassuringly, symptom burden in these children did not increase with time, and most recovered by day 56 [12].…”
Section: Discussionmentioning
confidence: 83%
“…Authors concluded that some children who tested positive for SARS-CoV-2 experience prolonged illness duration. Reassuringly, symptom burden in these children did not increase with time, and most recovered by day 56 [12].…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, Buonsenso et al [21] described preliminary evidence of long COVID in 68/129 Italian children, 120 days after they were diagnosed with confirmed SARS-CoV-2 infection. Finally, Molteni et al [22] reported the results of a comparative study from the UK. Of the 1,734 children tested positive for SARS-CoV2, 4.4% experienced illness duration ≥ 28 days after the acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study also reported that more than 50% of a cohort of 129 children had residual symptoms at follow-up 4 months after the initial diagnosis [21]. And in a study from the UK [22], 4.4% of 1,734 children who were positively tested for SARS-CoV2 experienced illness duration ≥ 28 days.…”
Section: Introductionmentioning
confidence: 95%
“…Most children who test positive for covid-19 and experience symptoms recover within a week, although a small proportion are unwell for more than four weeks, a study has found 1…”
mentioning
confidence: 99%